Trypanosomes and haemosporidia in the buzzard (Buteo buteo) and sparrowhawk (Accipiter nisus): factors affecting the prevalence of parasites - Svobodová, Milena; Weidinger, Karel; Peške, Lubomír; Volf, Petr; Votýpka, Jan; Voříšek, Petr (Parasitology research, 2015)
The prevalences of heteroxenous parasites are influenced by the interplay of three main actors: hosts, vectors, and the parasites themselves. We studied blood protists in the nesting populations of raptors in two different areas of the Czech Republic. Altogether, 788 nestlings and 258 adult Eurasian sparrowhawks (Accipiter nisus) and 321 nestlings and 86 adult common buzzards (Buteo buteo) were screened for parasites by the microscopic examination of blood smears and by cultivation. We examined the role of shared vectors and parasite phylogenetic relationships on the occurrence of parasites. In different years and hosts, trypanosome prevalence ranged between 1.9 and 87.2 %, that of Leucocytozoon between 1.9 and 100 %, and Haemoproteus between 0 and 72.7 %. Coinfections with Leucocytozoon and Trypanosoma, phylogenetically distant parasites but both transmitted by blackflies (Simuliidae), were more frequent than coinfections with Leucocytozoon and Haemoproteus, phylogenetically closely related parasites transmitted by different vectors (blackflies and biting midges (Ceratopogonidae), respectively). For example, 16.6 % buzzard nestlings were coinfected with Trypanosoma and Leucocytozoon, while only 4.8 % with Leucocytozoon and Haemoproteus and 0.3 % with Trypanosoma and Haemoproteus. Nestlings in the same nest tended to have the same infection status. Furthermore, prevalence increased with the age of nestlings and with Julian date, while brood size had only a weak negative/positive effect on prevalence at the individual/brood level. Prevalences in a particular avian host species also varied between study sites and years. All these factors should thus be considered while comparing prevalences from different studies, the impact of vectors being the most important. We conclude that phylogenetically unrelated parasites that share the same vectors tend to have similar distributions within the host populations of two different raptor species.
Keywords: Host Specificity; ptáci; Birds; Phylogeny; prevalence; Insect Vectors; nemoci ptáků; Female; zvířata; Haemosporida; Protozoan Infections, Animal; hostitelská specificita; Falconiformes; ženské pohlaví; hmyz - vektory; Male; fylogeneze; Czech Republic; Prevalence; Animals; Bird Diseases; Česká republika; mužské pohlaví; protozoální infekce zvířat; Simuliidae; Raptors; dravci; Trypanosoma